Can physical and psychological factors predict pain recurrence or an exacerbation of persistent non-specific low back pain? A protocol for a systematic review and meta-analysis - Deborah Falla; Michael Mansfield; Janet Deane; Kanya Wongwitwichote; Cho Wai Geoffrey Yu (BMJ Open)
Introduction Low back pain (LBP) is a global health concern. Approximately two-thirds of those who recover from LBP experience a relapse within a year, with many chronic cases encountering acute flare-ups (exacerbation). This systematic review will synthesise and analyse whether physical and/or psychological features can predict recurrent episodes of LBP or exacerbation of pain.Methods and analysis This systematic review protocol follows the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines. Comprehensive literature searches will be conducted in MEDLINE, EMBASE, APA PsycInfo, PubMed, CINAHL Plus, Web of Science, Scopus and ZETOC, spanning from each database’s inception through to January 2025. Google Scholar and grey literature sources, including OpenGrey, will also be searched to ensure comprehensive coverage. Two independent reviewers will screen titles, abstracts and full texts, assessing the risk of bias with a modified Quality in Prognosis Studies tool. The overall certainty of evidence will be evaluated using an adapted Grading of Recommendations Assessment, Development and Evaluation approach. If sufficient data homogeneity is present, a meta-analysis will be performed; otherwise, findings will be synthesised narratively. The results will identify the ability of physical and/or psychological factors to predict pain recurrence or acute exacerbation in case of persistent non-specific LBP.Ethics and dissemination This study protocol does not present any ethical concerns. The findings from the systematic review will be submitted for publication in a peer-reviewed journal and will also be presented at relevant conferences.PROSPERO registration number CRD42024599514.